A Newton-Multigrid algrithm for elasto-plastic/viscoplastic problems - Mahnken, Rolf (Computational Mechanics)
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

Dichroic photo- and electroluminescence of oligo p-(phenylene vinylene) derivatives - Lauhof, Marcus W.; Benning, Stephan A.; Kitzerow, Heinz-Siegfried; Vill, Volkmar; Scheliga, Felix; Thorn-Csányi, Emma (Synthetic Metals)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Spin-electronic devices with half-metallic Heusler alloys - Hütten, A.; Schmalhorst, J.; Thomas, A.; Kämmerer, S.; Sacher, Marc; Ebke, D.; Liu, N.-N.; Kou, X.; Reiss, G. (Journal of Alloys and Compounds)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Degradation of organic field-effect transistors made of pentacene - Pannemann, Ch.; Diekmann, T.; Hilleringmann, Ulrich (Journal of Materials Research)
This article reports degradation experiments on organic thin film transistors using the small organic molecule pentacene as the semiconducting material. Starting with degradation inert p -type silicon wafers as the substrate and SiO 2 as the gate dielectric, we show the influence of temperature and exposure to ambient air on the charge carrier field-effect mobility, on-off-ratio, and threshold-voltage. The devices were found to have unambiguously degraded over 3 orders of magnitude in maximum on-current and charge carrier field-effect mobility, but they still operated after a period of 9 months in ambient air conditions. A thermal treatment was carried out in vacuum conditions and revealed a degradation of the charge carrier field-effect mobility, maximum on-current, and threshold voltage.
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Degradation of organic field-effect transistors made of pentacene - Pannemann, Ch.; Diekmann, T.; Hilleringmann, Ulrich (Journal of Materials Research)
This article reports degradation experiments on organic thin film transistors using the small organic molecule pentacene as the semiconducting material. Starting with degradation inert p -type silicon wafers as the substrate and SiO 2 as the gate dielectric, we show the influence of temperature and exposure to ambient air on the charge carrier field-effect mobility, on-off-ratio, and threshold-voltage. The devices were found to have unambiguously degraded over 3 orders of magnitude in maximum on-current and charge carrier field-effect mobility, but they still operated after a period of 9 months in ambient air conditions. A thermal treatment was carried out in vacuum conditions and revealed a degradation of the charge carrier field-effect mobility, maximum on-current, and threshold voltage.
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Director reorientation of a side-chain liquid crystalline polymer under extensional flow - Cormier, Ryan J.; Schmidt, Claudia; Callaghan, Paul T. (Journal of Rheology)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Morphology and fluorescence quenching in photovoltaic samples containing fullerene and poly(p-phenylene-vinylene) derivatives - Röder, T; Kitzerow, Heinz-Siegfried; Hummelen, J.C (Synthetic Metals)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Structures with a minimum feature size of less than 100 nm in CVD-diamond for sensor applications - Otterbach, R.; Hilleringmann, Ulrich; Horstmann, T.J.; Goser, K. (Diamond and Related Materials)
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Mechanical Engineering; General Chemistry; Electronic; Optical and Magnetic Materials

Reactive ion etching of CVD-diamond for piezoresistive pressure sensors - Otterbach, R.; Hilleringmann, Ulrich (Diamond and Related Materials)
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Mechanical Engineering; General Chemistry; Electronic; Optical and Magnetic Materials

Strength difference in compression and tension and pressure dependence of yielding in elasto-plasticity - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics